2020
DOI: 10.1126/science.abc3753
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of protein-guided folding of the active site U2/U6 RNA during spliceosome activation

Abstract: Spliceosome activation involves extensive protein and RNA rearrangements that lead to formation of a catalytically-active U2/U6 RNA structure. At present, little is known about the assembly pathway of the latter and the mechanism whereby proteins aid its proper folding. Here we report the cryo-electron microscopy structures of two human pre-Bact complexes at core resolutions of 3.9-4.2 Å. These structures elucidate the order of the numerous protein exchanges that occur during activation, the mutually-exclusive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
83
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(95 citation statements)
references
References 56 publications
8
83
2
Order By: Relevance
“…Human GPATCH1 and DHX35 have both been identified in C complex spliceosomes assembled in vitro (Ilagan et al, 2013), while RBM5 and RBM17 have been found in the early A complex that includes U2 snRNP (Hartmuth et al, 2002). Loss of the nuclear exosome factor Rrp6 produced a signature that tended to cluster adjacent to that of strains lacking the ortholog of CTNNBL1 (Figure 3A-C), a core component of active human spliceosomes recently visualized by cryoEM (Townsend et al, 2020), indicating an overlap between RNA species normally degraded by Rrp6 and those that accumulate in cells lacking CTNNBL1. Other mutants also showed some degree of clustering, suggesting functional/biochemical relationships.…”
Section: Resultsmentioning
confidence: 94%
“…Human GPATCH1 and DHX35 have both been identified in C complex spliceosomes assembled in vitro (Ilagan et al, 2013), while RBM5 and RBM17 have been found in the early A complex that includes U2 snRNP (Hartmuth et al, 2002). Loss of the nuclear exosome factor Rrp6 produced a signature that tended to cluster adjacent to that of strains lacking the ortholog of CTNNBL1 (Figure 3A-C), a core component of active human spliceosomes recently visualized by cryoEM (Townsend et al, 2020), indicating an overlap between RNA species normally degraded by Rrp6 and those that accumulate in cells lacking CTNNBL1. Other mutants also showed some degree of clustering, suggesting functional/biochemical relationships.…”
Section: Resultsmentioning
confidence: 94%
“…This domain is atypical because the cluster of residues that are typically positively charged and coordinate nucleic acid binding in a winged helix is not charged, leading to the hypothesis that the highly conserved 3 10 helix is involved in protein binding [24] . KIN17 is predicted to have a disordered central region flanked by α-helices [15] , followed by a tandem of SH3-like domains separated by a flexible linker.…”
Section: Resultsmentioning
confidence: 99%
“…From B complex, the spliceosome undergoes a number of rearrangements through pre-Bact1, pre-Bact2, Bact and C complex. CryoEM studies of these complexes from human spliceosomes [2,15] allow for the study of different snapshots of the spliceosome assembly process. In these complexes there is an exchange of different factors that interact with the region of the 5'ss and its interactions with the U6 ACAGAGA box as the 5'ss is loaded into the catalytic core of the splicing machine.…”
Section: Introductionmentioning
confidence: 99%
“…Apparently, an opposite function of CBs is in place for the telomerase RNP, in which case CBs function to sequester telomerase from its nucleoplasmic substrates, the telomeres (Bizarro et al, 2019) Interestingly, two 2'-O-methyl groups within U2 snRNA are not impacted by Nopp140 KD, Gm12 and Gm25. In the active spliceosome, those 2'-O-methylated residues lie between helix Ia and Ib, and right adjacent to helix II formed between U2 and U6 snRNAs, perhaps pointing to an especially important role in splicing (Townsend et al, 2020;Zhang et al, 2017). In fact, U2-Gm12 was one of four 2'-O-methylated residues within the first 20 nucleotides of HeLa U2-snRNA that was required for in vitro splicing (Dönmez et al, 2004).…”
Section: Discussionmentioning
confidence: 99%